حصر بعض الأمراض الفيروسية المنتشرة في بساتين الحمضيات في الساحل السوري - حمدان, رحاب; إسماعيل, عماد (Latakia University Journal -Biological Sciences Series, 2019)
هدف البحث إلى التحري عن فيروسات تدهور الحمضيات (CTV) وتقزم الساتسوما (SDV) والورقة الممزقة (CTLV) المنتشرة في بساتين الحمضيات في الساحل السوري خلال عام 2010, وبلغ عدد العينات الكلي 336عينة. أظهرت نتائج اختبار البصمة النسيجية المناعية (TBIA) على العينات المختبرة انتشار فيروسات تدهور الحمضيات وتقزم الساتسوما والورقة الممزقة في بساتين الحمضيات في الساحل السوري وبنسب مختلفة, وسُجل في بانياس أعلى نسبة لانتشار فيروسي تدهور الحمضيات والورقة الممزقة في الحمضيات بنسب (35.37%) و(20.73)على التوالي, وكان فيروس تقزم الساتسوما أكثر انتشاراً في اللاذقية (22.06%). ولوحظ أن البرتقال البلدي أكثر إصابة بالتدهور, والبوميلو أكثر إصابة بفيروس تقزم الساتسوما, بينما سجلت أعلى نسبة إصابة بفيروس الورقة الممزقة في الحمضيات على الفالانسيا. وكان فيروس تدهور الحمضيات أكثر الفيروسات المدروسة انتشاراً في الساحل السوري ((25.89%. ويعد هذا البحث أول تسجيل لفيروسي تقزم الساتسوما والورقة الممزقة على الحمضيات في سورية. This research aimed to survey of Citrus tristeza virus (CTV), Satsuma dwarf virus (SDV), and Citrus tatter leaf virus (CTLV) distributed on citrus orchards in Syrian Coast during 2010. Total of surveyed samples was /336/. Results of tissue blot immune assay (TBIA) of tested samples showed the distribution of Citrus tristeza virus (CTV), Satsuma dwarf virus (SDV), and Citrus tatter leaf virus (CTLV) in citrus orchards in Syrian Coast in various ration. CTV and CTLV was most distributed in Banyas (35.37%), (20.73%). SDV was most distrusted in Lattakia (20.06%). Baladi orange was the most infected by CTV, pomelo was the most infected by SDV, when most infection by CTLV was recorded on Valencia. CTV was most studied viruses distribution in Syrian Coast (25.89%). This paper is the first record of SDV and CTLV on citrus in Syria.